Pengaruh Literasi Keuangan Syariah Dan Religiusitas Terhadap Minat Mahasiswa Menabung Di Bank Syariah (Studi Mahasiswa FAI UMSU) - Nabilah, Frisca Rahmani (AGHNIYA : Jurnal Ekonomi Islam, 2024)
This research aims to determine the influence of sharia financial literacy and religiosity on students' interest in saving in sharia banks, as well as to test and determine the effect of sharia financial literacy and religiosity simultaneously on students' interest in saving sharia in sharia banks. This research uses a quantitative approach with analytical tools multiple linear regression. The object of this research is students at the UMSU Faculty of Islamic Religion. The results of this research show that there is a partial influence between the variables of Islamic financial literacy and religiosity on students' interest in saving in Islamic banks and there is a simultaneous influence between the variables of Islamic financial literacy and religiosity on students' interest in saving in Islamic banks with the value of the Coefficient of Determination () of 0.436. This means that the influence of the variables sharia financial literacy and religiosity on students' interest in saving at sharia banks is 43.6%, while the remaining 56.4% is influenced by other unknown variables.